Mapping and genetic validation of a grain size QTL qGS7.1 in rice (Oryza sativa L.) - XUE, Pao; ZHANG, Ying-xin; LOU, Xiang-yang; ZHU, Ai-ke; CHEN, Yu-yu; SUN, Bin; YU, Ping; CHENG, Shi-hua; CAO, Li-yong; ZHAN, Xiao-deng (Journal of Integrative Agriculture, 2019)
Grain size is a major determinant of grain weight, which is one of the components of rice yield. The objective o this study was to identify novel, and important quantitative trait loci (QTLs) for grain size and weight in rice. QTLs were mapped using a BC4F4 population including 192 backcross inbred lines (BILs) derived from a backcross between Xiaolijing (XLJ) and recombinant inbred lines (RILs). The mapping population was planted in both Lingshui (Hainan, 2015) and Fuyang (Zhejiang, 2016), with the short- and long-day conditions, respectively. A total of 10 QTLs for grain length, four for grain width, four for the ratio of grain length to width, and 11 for grain weight were detected in at least one environment and were distributed across 11 chromosomes. The phenotypic variance explained ranged from 6.76–25.68%, 14.30–34.03%, 5.28–26.50%, and 3.01–22.87% for grain length, grain width, the ratio of grain length to width, and thousand grain weight, respectively. Using the sequential residual heterozygotes (SeqRHs) method, qGS7.1, a QTL for grain size and weight, was mapped in a 3.2-Mb interval on chromosome 7. No QTLs about grain size and weight were reported in previous studies in this region, providing a good candidate for functional analysis and breeding utilization.